Redescription of the male of Pikelinia tambilloi (Mello-Leitão, 1941) and its synonymy with Pikelinia toba Ramírez & Grismado, 1997 (Araneae: Filistatidae: Prithinae) - Grismado, Cristian J.; Ramírez, Martín J. (Zootaxa, 2006)
The male and female of Pikelinia tambilloi (Mello-Leitão, 1941) is redescribed from specimens recently collected in Santiago del Estero and Córdoba, Argentina. We report on variability in the internal female genitalia, and newly synonymize Pikelinia toba Ramírez & Grismado with P. tambilloi. The known range of P. tambilloi is thus widely extended. New records of P. kolla Ramírez & Grismado from Argentina are also reported.